Investigating Camel Superoxide Dismutase 1: A Computational Analysis of Potential Key Player in Heat Stress Adaptation: Investigating camel superoxide dismutase 1 - Yousaf, Muhammad Abrar; Khan, Muhammad Asjad (BioScientific Review, 2025)
Background. Superoxide dismutase 1 (SOD1) is crucial for cellular defense against oxidative stress induced by superoxide radicals, particularly in challenging conditions, such as elevated temperature and humidity. This study investigated SOD1 in Bactrian camel (Camelus bactrianus), Wild Bactrian camel (C. ferus), and Arabian camel (C. dromedarius) to understand its role in heat tolerance. Methodology. The current study employed bioinformatics analysis to assess the genomic features including GC% content. It also investigated the structure and location of the SOD1 gene on the chromosomes. Phylogenetic analysis was conducted to elucidate the evolutionary relationships based on SOD1 protein sequences. Structural analyses encompassed secondary and tertiary structure predictions, emphasizing stability and potential functional implications. Subcellular localization of the SOD1 protein was also explored. Results. C. dromedarius displayed the highest GC% in its genome, indicating improved thermostability. With the exception of C. bactrianus whose chromosomal location was unknown, all other species contained SOD1 gene on their first chromosome. Based upon SOD1 protein sequences, phylogenetic investigation emphasized the close evolutionary link within the Camelidae family. Structurally, all three species of camel shared an acidic, globular, and thermally-stable SOD1 protein having high glycine content and lack of cleavage sites. Analysis of secondary structure indicated a frequency of random coils, highlighting the adaptability and evolutionary conservation of protein. Predictions of tertiary structure verified that SOD1 was stable in all species. The protein is predominantly found in cytoplasm although, also present in nucleus, extracellular region, and mitochondria. Conclusion. This inclusive analysis of SOD1 in three different species of camel highlighted their strong adaptation to desert environment by elucidating their genomic and proteomic stability. Further research is necessary to investigate the biochemical mechanisms behind camels’ extraordinary ability to thrive in desert conditions and respond to the challenges posed by climate change.